Algorithm for assessing the prospects of offshore oil and gas projects in the Arctic - Alina Ilinova; Amina Chanysheva (Energy Reports, 2020)
Russia is one of the key players in the Arctic with ambitions to continue development its Arctic oil resources. Nowadays the only fully launched oil and gas offshore project in Russia is the platform Prirazlomnaya, a number of other projects are at the various stages of realization and their prospects remain unclear today. There are a number of factors that are preventing Russia from fully developing its offshore Arctic oil potential. The aim of this paper is to create a methodological base for assessment of prospects of Arctic offshore projects. We develop an algorithm for such assessment, which consists of three stages: (i) general expert survey; (ii) informational basis development; (iii) specific expert survey. We are focusing on the specific features of the Arctic oil and gas projects, possibilities of using existing forecasting methods, as well as on the complex approach to our research. Keywords: Forecasting, Shelf, Arctic, Oil and gas projects, Algorithm, Hydrocarbon resources, Prospects